2012
DOI: 10.1097/mat.0b013e31826d6070
|View full text |Cite
|
Sign up to set email alerts
|

Alloimmunosensitization in Left Ventricular Assist Device Recipients and Impact on Posttransplantation Outcome

Abstract: Left ventricular assist devices (LVADs) have become an established surgical therapy for patients with end-stage heart failure who require hemodynamic support as a bridge-to-transplant or destination therapy. However, the anatomic and physiologic consequences of long-term LVAD support have yet to be fully clarified. Despite the clinical success of these devices, it has been reported that many patients bridged to transplantation with mechanical support develop circulating antibodies with potential donor reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“… found that patients with LVADs did not have increased rejection episodes, allograft vasculopathy, or decreased survival after transplantation, as compared to non‐bridged patients. This is supported by larger reviews by the ISHLT, which found that LVAD patients had higher rates of sensitization (16.6% vs. 7.6%) but no differences in mortality . A more recent study by Shankar et al.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“… found that patients with LVADs did not have increased rejection episodes, allograft vasculopathy, or decreased survival after transplantation, as compared to non‐bridged patients. This is supported by larger reviews by the ISHLT, which found that LVAD patients had higher rates of sensitization (16.6% vs. 7.6%) but no differences in mortality . A more recent study by Shankar et al.…”
Section: Discussionmentioning
confidence: 77%
“…Pre‐orthotopic heart transplant (OHT) LVAD implantation is known to increase pre‐transplant PRA levels . Although it is well documented that women tend to have a higher pre‐transplant PRA levels than men, LVAD‐induced rise in PRA levels appears to affect both genders equally .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the era of first generation LVAD support, reports indicated that these elevated levels of antibodies were linked to poorer outcomes, notably graft rejection. This association is less clear in modern studies; while some have indicated that this difference may not be significant, other studies have noted an increased level of antibody-mediated rejection in the setting of increased sensitization [52]. This remains an issue of considerable controversy.…”
Section: Allosensitizationmentioning
confidence: 98%
“…rituximab) or intravenous immunoglobulins (IVIG) target anti-HLA antibodies indirectly [20]. The trend of immunologically incompatible organ replacement with good short-term results is meanwhile widespread for kidney transplantations based on a broad understanding of the principles of sensitization and desensitization [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%